1996
DOI: 10.1346/ccmn.1996.0440513
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineral Diagenesis and Thermal History of the Thonex Well, Western Swiss Molasse Basin

Abstract: Abstract--Results are presented of a diagenetic study from the 1300 m thick Oligocene Molasse deposits penetrated by the Th6nex geothermal exploration well (Geneva, Switzerland). The x-ray diffraction (XRD) studies of fine-grained rocks indicate the following diagenetic changes: a decrease of illite/smectite (US) expandability from approximately 90% to 30% with depth, a decrease of the amount of US in the clay mineral fraction, and the appearance of corrensite at depths >750 m. The transition from random US to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Similar conditions have been observed in wells in the Swiss (Rybach, 1984;Schegg, 1994;Schegg and Leu, 1996;Schegg et al, 1997), German (Jacob and Kuckelkorn, 1977;Teichmueller and Teichmueller, 1986), and Austrian Molasse Basin and its fold and thrust belt (Sachsenhofer, 2001).…”
Section: Oligocene and Miocene Heat Flowssupporting
confidence: 70%
“…Similar conditions have been observed in wells in the Swiss (Rybach, 1984;Schegg, 1994;Schegg and Leu, 1996;Schegg et al, 1997), German (Jacob and Kuckelkorn, 1977;Teichmueller and Teichmueller, 1986), and Austrian Molasse Basin and its fold and thrust belt (Sachsenhofer, 2001).…”
Section: Oligocene and Miocene Heat Flowssupporting
confidence: 70%
“…In this well, the disappearance of smectite (R0), which marks the transition between zones R0 and R1, took place at a maximum temperature of 160ºC (Fig. 8), much higher than the values of 75À120ºC reported in the literature (Hoffman & Hower, 1979;Ś rodoń & Eberl, 1984;Schegg & Leu, 1996;Uysal et al, 2000b;Abid et al, 2004).…”
Section: Thermal Modelling and Clay Mineralogymentioning
confidence: 56%
“…oil or gas generation and possible paths of hydrocarbon migration (Tissot et al, 1987;Waples et al, 1992;Yahi et al, 2001). Temperature values obtained from these models have frequently been related to clay mineral distribution in diagenetic series (Pearson & Small, 1988;Glansman et al, 1989;Velde & Lanson, 1993;Schegg & Leu, 1996) and to organic maturity indicators, mainly vitrinite reflectance (Gier, 2000). Although a direct correspondence between time/ temperature and organic maturity exists in many sedimentary basins, correspondence with clay mineral composition is not as common, as it depends on several additional factors (Scotchman, 1987;Merriman, 2005).…”
mentioning
confidence: 99%
“…It has been suggested that the temperature that reflects the appearance of R1 I/S during the smectite illitization process is generally around 100 °C while the transition temperature from R1 to R3 I/S can be up to ca. 180 °C [48,50,[53][54][55]. In this study, most of the studied samples have the R1 ordered I/S, except for only one sample that has the R3 ordered I/S (Table 1) indicating that the paleo-diagenetic temperature for the studied samples could have been up to 180 °C but for most of the samples, this value ranges from 100 to 180 °C.…”
Section: Implications For Paleo-diagenetic Temperaturementioning
confidence: 56%
“…Temperature and fluid chemistry thus should be the dominant factors that would have influenced the formation of I/S in this study. Many studies have focused on the diagenetic temperature during the burial process, using the evolution of smectite illitization (especially the percentages of smectite layers within I/S) [48,50,[53][54][55]. In the XRD patterns for the EG-saturated clay fractions, as smectite layers decrease in I/S, the peaks at 9 Å, as well as peaks at 5 Å, become sharp and narrow showing a trend towards illite and indicating a progressive increment in temperature (Figure 7).…”
Section: Implications For Paleo-diagenetic Temperaturementioning
confidence: 99%